Ageing and development in a society for all ages (ECLAC SantiagoCL, 2007)
Presents and analyzes the information available on the demographic ageing process, the situation of the older adult population and the progress made by the countries in applying the Regional Strategy for the Implementation in Latin America and the Caribbean of the Madrid International Plan of Action on Ageing.
Bibliography: p. 37-40